Pain duration is associated with increased muscle sympathetic nerve activity in patients with Achilles tendinopathy. (28th December 2016) - Jewson, J. L.; Lambert, E. A.; Docking, S.; Storr, M.; Lambert, G. W.; Gaida, J. E.
Abstract : Tendinopathy is a common condition, which has been linked to surrogate measures of sympathetic nervous system (SNS) activity and insulin resistance. This study aimed to compare in vivo measures of the SNS and insulin resistance between individuals with and without Achilles tendinopathy. This case–control study compared Achilles tendinopathy sufferers to healthy controls. SNS activity was quantified using muscle sympathetic nerve activity (MSNA), while metabolic status was assessed via a modified glucose tolerance test and fasting lipid panel. Ultrasound tissue characterization assessed tendon structure. Resting MSNA did not differ between the 15 cases and 20 controls. Tendon pain duration in tendinopathy patients was correlated with burst frequency ( R 2 =.32, P =.02) and burst incidence ( R 2 =.41, P =.01) of MSNA. After adjusting for multiple comparisons, there was a trend suggesting fasting glucose was greater in cases (median 4.80, IQR .70 in cases vs 4.51, .38 in controls) and correlated with pain severity ( R 2 =.14, P =.03), but no other metabolic measures were associated with tendon pain/structure. This study indicates that SNS activity is associated with tendon pain duration, building on previous data indicating the SNS is involved in recalcitrant tendinopathy. Metabolic parameters had little relationship with Achilles tendinopathy in this metabolically homogenous sample. Prospective studies are required to uncover the precise relationship between SNS activity, insulin resistance, and tendinopathy.